A band‐suppression UWB suspended planar antenna incorporating a slotted spiral resonator. Issue 5 (19th November 2012) - See, C. H.; Abd‐Alhameed, R. A.; Hraga, H. I.; Excell, P. S.; Jones, S. M. R.; Noras, J. M.
Abstract A novel miniaturized planar inverted F‐L antenna assembly is considered for UWB radio operations. The antenna design utilizes the electromagnetic coupling between an air dielectric planar inverted‐F antenna (PIFA) and a parasitic planar inverted‐L (PIL) element, with broadband feeding from a rectangular plate. To improve the functionality of the channel, a simple notch filter has been introduced through a local modification to the broadband feed plate, this takes the form of a simple slotted rectangular spiral resonator which is etched directly onto the plate. This allows the proposed antenna to maintain its full band UWB coverage, with the HYPERLAN/2 band centered at 5.35 GHz to be effectively rejected over the sub‐band 5.15–5.725 GHz, without the need for substantial re‐optimization of its principal structure parameters. The impedance bandwidth operates over the full UWB band, with VSWR better than 2, this performance is not degraded by the presence of the band rejection. The observed gains, radiation patterns, and group delay confirm that the antenna has appropriate characteristics for short range wireless applications. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.